Power conditioning of thermoelectric generated power using dc-dc converters: a case study of a boost converter - Twaha, Ssennoga; Zhu, Jie; Yan, Yuying (2016)
The near exhaustion of non-renewable energy resources such as fossil fuels followed by disastrous climatic changes have alerted the world to invest in alternative energy sources. Thermoelectric (TE) technology is responsible for innovating TE devices such as thermoelectric generators (TEGs) which are used to generate electrical energy from heat in an environmentally friendly manner. One of the challenges behind TEG is that they have low efficiency due to low figure of merit. Moreover the power generated is unstable and therefore needs proper power conditioning mechanism before it is connected to the load. The objective of this work is to analyze the performance of a boost dc-dc converter connected on TEG system. The simplified models have been used as the basis of TEG design. Results indicate that the converter is able to stabilize and boost the voltage and higher converter efficiencies are achieved at different hot side temperatures.